Reduction of Losses and Improvement of Voltage Profile in Radial Distribution Network by Interconnection of Feeders - Mecon Joshi; Manoj Godar (KEC Journal of Science and Engineering, 2025)
High penetration of photovoltaic systems is creating various issues in the distribution network such as increased power losses and violation of voltage limits. The voltage violation occurs at the point of common coupling in the network especially at midday when the photovoltaic generation is high and the loading of the network is low. The approach considered in this paper to mitigate these issues is by the interconnection of radial feeders. The interconnection of feeders allows the direct connection of areas having high photovoltaic power output to areas with high loading at midday. When the position is properly chosen, the interconnection reduces the network losses and also mitigates the voltage violation at the susceptible areas. In this paper, the CIGRE low-voltage European distribution network has been considered and its three subnetworks have been interconnected in various configurations. The interconnection minimized the daily network losses by 17.28% at the optimum case and was also successful in mitigating overvoltage in the network. The working mechanism of this approach is straightforward while giving the desired results.